The world of the cell - Becker, Wayne M.
The World of the Cell, Fourth Edition, helps students understand and enjoy cell biology. Focusing on core concepts, the authors present solid information without being encyclopedic. Thoroughly updated, the Fourth Edition continues the text's tradition of clarity and readability, and extends its effectiveness as a learning tool by dividing material in each chapter into a series of conceptual sections, each introduced by a sentence heading that summarizes the concept